Health-related quality of life and patient-centred outcomes with olaparib maintenance after chemotherapy in patients with platinum-sensitive, relapsed ovarian cancer and a BRCA1/2 mutation (SOLO2/ENGOT Ov-21): a placebo-controlled, phase 3 randomised trial. Issue 8 (August 2018) - Friedlander, Michael; Gebski, Val; Gibbs, Emma; Davies, Lucy; Bloomfield, Ralph; Hilpert, Felix; Wenzel, Lari B; Eek, Daniel; Rodrigues, Manuel; Clamp, Andrew; Penson, Richard T; Provencher, Diane; et al.
Summary: Background: In the phase 3 SOLO2 trial (ENGOT Ov-21), maintenance therapy with olaparib tablets significantly prolonged progression-free survival (primary endpoint) compared with placebo in patients with a germline BRCA1 or BRCA2 ( BRCA1/2 ) mutation and platinum-sensitive, relapsed ovarian cancer who had received two or more lines of previous chemotherapy. The most common subjective adverse effects included fatigue, nausea, and vomiting, which were typically low grade and self-limiting. Our a-priori hypothesis was that maintenance olaparib would not negatively affect health-related quality of life (HRQOL) and additionally that the prolongation of progression-free survival with olaparib would be underpinned by additional patient-centred benefits. Methods: In SOLO2, 196 patients were randomly assigned to olaparib tablets (300 mg twice daily) and 99 to placebo. Randomisation was stratified by response to previous chemotherapy (complete vs partial) and length of platinum-free interval (>6–12 vs >12 months). The prespecified primary HRQOL analysis evaluated the change from baseline in the Trial Outcome Index (TOI) score during the first 12 months of the study. To be assessable, patients had to have an evaluable score at baseline and at least one evaluable follow-up form. Secondary planned quality-of-life (QOL) analyses included the duration of good quality of life (defined as time without significant symptoms of toxicity [TWiST] and quality-adjusted progression-free survival [QAPFS]). Efficacy and QOL outcomes were analysed in all randomly assigned patients (the full analysis set), and safety outcomes were analysed in all randomly assigned patients who received at least one dose of study drug. This ongoing study is registered withClinicalTrials.gov, numberNCT01874353, and is closed to new participants. Findings: The adjusted average mean change from baseline over the first 12 months in TOI was −2·90 (95% CI −4·13 to −1·67) with olaparib and −2·87 (–4·64 to −1·10) with placebo (estimated difference −0·03; 95% CI −2·19 to 2·13; p=0·98). Mean QAPFS (13·96 [SD 10·96] vs 7·28 [5·22] months; difference 6·68, 95% CI 4·98–8·54) and mean duration of TWiST (15·03 [SD 12·79] vs 7·70 [6·42] months; difference 7·33, 95% CI 4·70–8·96) were significantly longer with olaparib than with placebo. Interpretation: Olaparib maintenance therapy did not have a significant detrimental effect on HRQOL compared with placebo. There were clinically meaningful patient-centred benefits in both TWiST and QAPFS despite the adverse effects associated with olaparib. These patient-centred endpoints support the improvement in progression-free survival, the primary endpoint in SOLO2, and should be included in future trials of maintenance therapies. Funding: AstraZeneca.